Front cover: Proteomics of the red blood cell carbonylome during blood banking of erythrocyte concentrates. Issue 3 (1st March 2016) - Delobel, Julien; Prudent, Michel; Tissot, Jean‐Daniel; Lion, Niels
Abstract : DOI:10.1002/prca.201500074 Red blood cells stored for transfusion suffer from oxidative stress. Oxidized proteins were isolated at different steps of storage through biotin hydrazine derivatization and analyzed by gel‐based proteomics. Carbonylation affects proteins involved in antioxidant defenses, metabolism pathways and proteasomal degradation. The 3D protein structure was taken from the EMBL‐EBI website (http://www.ebi.ac.uk/pdbe/entry/pdb/1U8F ). Further details can be found in the article by Julien Delobel, Michel Prudent, Jean‐Daniel Tissot and Niels Lion on page 257.